Radical Cystectomy in England from 2013 to 2019 on 12, 644 patients: An analysis of national trends and comparison of surgical approaches using Hospital Episode Statistics data. Issue 5 (12th March 2021) - Tamhankar, Ashwin Sunil; Thurtle, David; Hampson, Alexander; El‐Taji, Omar; Thurairaja, Ramesh; Kelly, John D.; Catto, James W. F.; Lane, Tim; Adshead, James; Vasdev, Nikhil
Abstract: Introduction: We evaluate the data of 12, 644 Radical Cystectomies in England (Open, Robotic and Laparoscopic) with trends in the adaption of techniques and post‐operative complications. Methods: This analysis utilised national Hospital Episode Statistics (HES) from NHS England. Results: There was a statistically significant increase ( P < .001) in the number of Robotic assisted radical cystectomies from 10.8% in 2013‐2014 and 39.5% in 2018‐2019.The average LOS reduced from 12.3 to 10.8 days for RARC from 2013 to 2019 similarly the LOS reduced from 16.2 to 14.3 for ORC. The rate of sepsis (0‐90 days) did rise from 5% to 14.5% between 2013‐2014 and 2017‐2018 for the entire cohort ( P < .001). Acute renal failure (ARF) increased over the years from 9.5% to 17% ( P < .001). The rate for fever, UTI, critical care activity and ARF were higher for ORC than RARC ( P < .001).The comparison of all episodes within 90 days for conduit versus non‐conduit diversions showed significantly higher rates of sepsis, infections, UTI and fever in non‐conduit group .Overall complications were significantly higher in non‐conduit group throughout the duration except was year 2016‐17( P < .001).The robotic approach has increased in last 5 years with nearly 40% of the cystectomies now being robotically in 2018‐19 from the initial percentage of 10.8% in 2013‐14. Conclusion: This evaluation of the HES data from NHS England for 12, 644 RC confirms an increase in the adoption of Robotic Cystectomy. Our data confirms the need to develop strategies with enhanced recovery protocols and post‐operative close monitoring following Radical Cystectomy in order to reduce post‐operative complications.